2014
DOI: 10.4315/0362-028x.jfp-14-086
|View full text |Cite
|
Sign up to set email alerts
|

Sample Preincubation Strategy for Sensitive and Quantitative Detection of Clenbuterol in Swine Urine Using a Fluorescent Microsphere–Based Immunochromatographic Assay

Abstract: We describe an ultrasensitive and quantitative immunochromatographic assay to determine the amount of clenbuterol (CLB) in swine urine. In this study, fluorescein isothiocyanate polystyrene fluorescent microspheres were used as probes. A sample preincubation strategy was introduced to this immunochromatographic assay. Results showed that the strategy evidently improved the sensitivity and accuracy of lateral flow assay. The method was completed in 20 min, and a half-maximal inhibitory concentration of 0.13 μg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…Therefore, the concentration of the RP should be optimized. Interestingly, the peak area ratio of test line to control line (P T /P C ) for evaluating miR-21 levels was more precious because it eliminated the effects of immunoreaction dynamics parameters (the efficiencies of antibody-antigen interactions on test line and control line) [ 34 ]. As shown in Fig 2 , background signals decreased as RP probe concentrations decreased from 80 to 50 nM.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the concentration of the RP should be optimized. Interestingly, the peak area ratio of test line to control line (P T /P C ) for evaluating miR-21 levels was more precious because it eliminated the effects of immunoreaction dynamics parameters (the efficiencies of antibody-antigen interactions on test line and control line) [ 34 ]. As shown in Fig 2 , background signals decreased as RP probe concentrations decreased from 80 to 50 nM.…”
Section: Resultsmentioning
confidence: 99%
“…In the proposed format, the detected complexes are formed after the sample has rapidly moved along the tracks on the working membrane between neighboring zones, which are only 2 mm apart. Several immunochromatographic tests that exclude the conjugate pad have been reported [13][14][15]. In these assays, the conjugate is preincubated with the sample beyond the test strip.…”
Section: Discussionmentioning
confidence: 99%
“…Pre-incubation was successfully used in a competitive format of LFIA for the detection of veterinary drug residues (clenbuterol, sulfadiazine, and tetracycline) [ 14 ], the aptamer-based detection of β-conglutin [ 15 ] and aflatoxin B1 [ 16 ], and the simultaneous detection of five chemicals in drinking water [ 17 ]. Dentg et al showed that the LOD decreased by 3.5 times in clenbuterol detection (i.e., using five minutes pre-incubation) in comparison with the conventional LFIA [ 18 ]. Zvereva et al presented a LOD that decreased by 14 times in ractopamine detection [ 19 ], which confirmed the pre-incubating approach.…”
Section: Introductionmentioning
confidence: 99%